Poets of Bifurcated Tongues, or on the Plurilingualism of Canadian-Hungarian Poets - Kürtösi, Katalin (TTR)

(untitled) (Association canadienne de traductologie, 1993)
AbstractPoets of Bifurcated Tongues, or on the plurilingualism of Canadian-Hungarian Poets — This article aims at an analysis of the plurilingualism of four poets of Hungarian origin, living in Canada: Robert Zend, George Vitéz, László Kemenes Géfin and Endre Farkas. Before examining the poems themselves, the various concepts of plurilingualism and the aspects of grouping these poems, including the code-switching strategies used in them, are reviewed. The base language and the nature of code-switching is discussed with a special emphasis on the relationship of grammatical units, intra- and intersentential switches within contexts where plurilingualism occurs. The first three poets have become bilinguals as adults: they form part of Hungarian literature as well as of Canadian writing. The last one, however, has a childhood bilingualism and is considered an English-Canadian Poet. Since they have a twofold minority status (Hungarian origins, plus writing in English in Montréal), analysis of these poets requires a special approach. The main hypothesis of the article is that, when using more than one language within the same work, the author is able to reach special effects which would be otherwise impossible. These poems, plurilingual in nature, also show that, for these authors, language is of multiple use: not only is language a tool of communication, but also the theme of some of their poems: they are often self-reflexive, making formal and semantic experimentation possible.